Answer: (x - y)² = 6
Concept:
Here, we need to know the concept of FOIL.
It is a way to expand squared or greater exponents parenthesis.
Explanation:
Given information
x² + y² = 20
xy = 7
Given expression
(x - y)²
Expand parenthesis through FOIL
= (x - y) (x - y)
= x · x - x · y - x · y + y · y
= x² - 2xy + y²
Substitute values into the expression
= x² + y² - 2xy
= (20) - 2 (7)
= 20 - 14
=
![\boxed{6}](https://img.qammunity.org/2023/formulas/mathematics/college/7t6hhw7nb11xaej4mxghgrdpr1qvsgenv8.png)
Hope this helps!! :)
Please let me know if you have any questions